2005
DOI: 10.1007/bf02893856
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of Tenascin-C in glioblastoma: Correlation with angiogenesis and tumor cell proliferation

Abstract: Tenascin-C (TN-C) is an extracellular matrix protein which participates in different processes like normal fetal development, wound healing, inflammation, keloids and rheumatoid arthritis. Furthermore, the immunostaining for TN-C is seen in the stroma of various malignant tumors as in glioblastoma multiforme (GBM), however, the significance of these findings is still not clear. In this study 62 GBM samples were analyzed immunohistochemically for distribution patterns of TN-C and correlated with angiogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…These proteins are highly specific to GBM irrespective of their location in brain, thus providing important insights into the disease pathology as has been demonstrated by the validated proteins and their involvement in various events of tumorigenesis. Our analysis also provided several other upregulated proteins, like SERPH, PDIA1, CERU, TENA, VTNC, APOE, LEG1, HRG, and FKBP5, that are known to be involved in tumor progression, aggressiveness, and invasion in GBM (3,17,18,28,30,32,39,45,47). In addition to known GBM-associated proteins, novel potential biomarkers identified in this study include CLIC4, NP1L1, IGKC, TAGL2, and YES (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 85%
“…These proteins are highly specific to GBM irrespective of their location in brain, thus providing important insights into the disease pathology as has been demonstrated by the validated proteins and their involvement in various events of tumorigenesis. Our analysis also provided several other upregulated proteins, like SERPH, PDIA1, CERU, TENA, VTNC, APOE, LEG1, HRG, and FKBP5, that are known to be involved in tumor progression, aggressiveness, and invasion in GBM (3,17,18,28,30,32,39,45,47). In addition to known GBM-associated proteins, novel potential biomarkers identified in this study include CLIC4, NP1L1, IGKC, TAGL2, and YES (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 85%
“…Tenascin-C is expressed in more than 90% of gliomas and its expression increases with increasing tumor grade. Although its functions remain controversial, recent studies suggest that it plays a role in several cellular processes, including adhesion, migration and proliferation [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al discovered that TN-C regulates the expression of VEGF 85 and Behrem et al showed that TN-C has an influence on VEGF action and that the microvascular density shows a dependency of TN-C expression. 86 Additionally to the high expression of TN-C in glioma blood vessels the known receptor for TN-C, integrin a v, is found in elevated levels in glioma tissue, as well as the protein periostin. 77 Periostin was detected as a promoter of TN-C incorporation into the ECM and to organize the architecture of the ECM.…”
Section: Tn-c In Tumor Angiogenesismentioning
confidence: 99%